Unveiling the Determinants of Green Entrepreneurship: An Exploratory Study in the Tunisian Context - Tira, Houda Nouicer; Fessi, Imen; Abdelghani, Tamer M.; Sobaih, Abu Elnasr E. (Journal of Management World, 2025)
This study explores the determinants of green entrepreneurship among Tunisian Eco-entrepreneurs. These determinants are approached from the angle of Ajzen’s theory of planned behavior (1991) through the factors of entrepreneurial attitude, subjective norms and perceived control of behavior. The research explores the reasons, which lead entrepreneurs to choose the ecological concept. A qualitative study was conducted via semi-structured interviews with a group of 22 eco-entrepreneurs. The study was based on voluntary respondents chosen by non-probability sampling. Thematic content analysis method was used to analyze the collected data and identify the main determinants. The results of this study revealed that green values are key determinant and explanatory of the favorable attitude towards green entrepreneurship. Contrary to the studies of traditional entrepreneurship in which the pressure of the social environment does not play a determining role and does not affect the decision to undertake in the green, whereas a strong feeling of perceived self-efficacy determines and encourages this direction. This study allows on a practical level through an understanding of attitude, subjective norms and perceived control of behavior, to understand what drives or hinders the orientation towards green entrepreneurship. Thus, the actors involved in entrepreneurship in Tunisia can better design programs and action plans to strengthen and increase commitment in this promising sector.